Application of multi-leaf foil bearings in high-speed turbo-machinery - Yu GUO; Yu HOU; Qi ZHAO; Xionghao REN; Tianwei LAI (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2020)
Foil bearings, featuring various advantages (such as high-speed, good operation stability, low friction, long life, strong adaptability, wide temperature range, and oil-free), are promised to have good development prospects and application in high-speed centrifugal machinery. In order to evaluate the actual performance of the multi-leaf foil bearings and promote their further application in the high-speed turbo-machinery, the experimental research of multi-leaf foil bearings with rotor diameter of 25 mm are conducted in this paper. The static and transient tests of the multi-leaf journal bearings with different foil thickness are initiated on the journal bearing test rig to analyze their characteristics, such as the load-deflection, bearing Coulomb friction, start-up and operating friction torque, which could provide guidance for the structural parameter design and exploitation of the bearing. Afterwards, two different bearing combinations are adopted as the supporting components, namely A-type: multi-leaf foil journal bearing with aerostatic thrust bearing and B-type: multi-leaf foil journal bearing with multi-leaf foil thrust bearing. They are applied in the high-speed turbo machinery with the rotor diameter of 25 mm to assess the direct application of the multi-leaf foil bearings in high-speed turbo-machinery. The transient speed-up, high speed, and speed-down experiments of the rotor-bearing system are conducted and their transient characteristics and stability are compared. The experimental results indicate that the start-up (0.6x10-2~1.8x10-2N·m) and steady operation frictional torque (0.25x10-2~0.5x10-2N·m) of the multi-leaf foil journal bearing is relative small; the impeller-rotor system operates steadily and smoothly with good repeatability, supported by A-type and B-type, the maximum rotor speed at about 94krpm achieved in the tests is close under the support of A-type and B-type. However, there are smaller main frequency amplitude, nonsynchronous amplitude and better rotor orbit in the transient processes with the support of B-type, which indicates better stability.